Clinical Pathway Implementation in ACS STEMI Patients - Wiedya Kristianti Angeline; Martina Martina; Ermi Girsang; Ali Napiah Nasution (Universitas Aisyah Pringsewu, 2022)
Delay in handling patients with Acute ST-elevation myocardial infarction (STEMI) is the cause of high mortality and the incidence of MACE (Major Adverse Cardiac Event), so efforts are needed to reduce it by handling patients with Acute Coronary Syndrome (ACS) with the implementation of clinical pathways. This study evaluates the application of clinical pathways for ACS STEMI patients based on content and quality and evaluates the effectiveness of clinical pathways based on length of stay, total costs, and outcomes between ACS STEMI patients with clinical pathways and non-clinical pathways. This research uses mixed methods with an exploratory sequential approach. Evaluation of clinical pathways for ACS STEMI patients with a qualitative approach through in-depth interviews using the Integrated Care Pathway Appraisal Tool (ICPAT) questionnaire. Furthermore, a comparative approach is used to determine the effectiveness of clinical pathways based on length of stay, total costs and outcomes (outcomes) between ACS STEMI patients who have and do not have a clinical pathway. The study was conducted from November 2021 to April 2022 at the Cardiology Section of Murni Teguh Hospital, Medan. The results show that the implementation process is of good quality, but the content still needs to be improved. From the test results with the Mann-Whitney U Test, it can be seen that there is an effect of using the application of clinical pathways on length of stay, total costs and outcomes in ACS STEMI patients. It is suggested to the hospital management to determine a strategy to increase the compliance of doctors and nurses to the clinical pathway. Abstrak: Keterlambatan penanganan pasien Acute ST-elevation myocardial infarction (STEMI) menjadi penyebab tingginya mortalitas dan kejadian MACE (Major Adverse Cardiac Event), maka diperlukan upaya dalam menguranginya melalui penanganan pasien Acute Coronary Syndrome (ACS) dengan diberlakukannya clinical pathway. Penelitian ini bertujuan mengevaluasi penerapan clinical pathway pasien ACS STEMI berdasarkan konten dan kualitas serta mengevaluasi efektivitas clinical pathway berdasarkan lama rawat, biaya total dan hasil antara pasien ACS STEMI dengan clinical pathway dan non clinical pathway. Penelitian ini menggunakan mix methods dengan pendekatan exploratory sequential. Evaluasi clinical pathway pasien ACS STEMI dengan pendekatan kualitatif melalui wawancara mendalam menggunakan kuesioner Integrated Care Pathway Appraisal Tool (ICPAT). Selanjutnya pendekatan komparatif digunakan untuk mengetahui efektivitas clinical pathway berdasarkan lama rawat, biaya total dan hasil (outcomes) antara pasien ACS STEMI yang memiliki dan tidak memiliki clinical pathway. Studi dilakukan selama bulan November 2021 hingga April 2022 di Bagian Kardiologi Rumah Sakit Murni Teguh Medan. Hasil penelitian menunjukkan proses implementasi yang dilakukan sudah baik untuk mutu, namun konten masih perlu ditingkatkan. Dari hasil uji dengan Mann Whitney U Test terlihat bahwa ada pengaruh penggunaan penerapan clinical pathway terhadap lama rawat, biaya total dan hasil pada pasien ACS STEMI. Disarankan pada pihak manajemen rumah sakit untuk menentukan strategi dalam meningkatkan kepatuhan dokter dan perawat terhadap clinical pathway.